Evaluation of the Lift Programme : Phase 3 Report: The Effectiveness and Efficiency of the Lift Programme. Summary.: Phase 3 Report: The Effectiveness and Efficiency of the Lift Programme. Summary. Social Research Number: 35/2018 (2018) - Allies, Oliver; Dr, Engeli, Andrew
No abstract available